Formulation and Evaluation of In-Situ Gel for Periodontal Disease - Puri G. Ashutosh; Dr. Sandeep C Atram; Mandwe S. Vrushabh; Bhonde G. Akash; Bawankar V.Dipali (Asian Journal of Pharmaceutical Research and Development, 2025)
Purpose: The main objective of present study is to formulate and evaluate Carbopol and Methyl cellulose based In-situ periodontal gel of Atorvastatin calcium. Approach: The In-situ gel was prepared by using different concentrations of Polymeric mixture of Carbopol and Methyl cellulose In-situ gel in solution state was evaluated for Gelling capacity, Gelling temperature, Gelling time, % Drug content and Syringeability and gel was evaluated for Physical appearance, pH, Viscosity and rheology, Spreadability, % Drug content, In vitro drug release and drug release kinetics. Findings: Compatibility study was performed using FTIR and DSC, so results showed there was no interaction between drug and other excipients. Gelation time and temperature was found in the range of 6-8 min and 34-37ºC respectively.The Physical appearance of all formulations was cloudy except F3 and F3 was found to be clear. The pH of all formulations was found in the range of 5.6-5.8. All the formulation except formulation F6 showed satisfactory syringeability due to lower concentration of polymers.Viscosity of all formulations was found in the range of 1254.3 to 5680.8 centipoise at 37±1ºC at 5 to 30RPM and all formulations exhibited pseudoplastic behaviour. Based on the results of release study, formulation F5 was found to be optimum formulation as it released 68.63% drug at the end of 18 hr. In vitro release study revealed that release rate of drug from the In-situ gel was concentration dependent; as concentration of Carbopol increased and Methyl cellulose decreased, the drug release rate was retarded upto 6 hr study. Conclusion: It can be concluded that formulation containing 2% w/v Gel base of 1.8g of Carbopol-940 and 0.2g of Methyl cellulose dissolved in 100ml of Distilled water gave optimized formulation.